Building an Equitable Forest: Advancing Social Justice through Recognition in Indigenous Forest Management Practices in an Old-Balinese Village - Suyadnya, I Wayan; Prianti, Desi Dwi; Kanto, Sanggar (Universitas Udayana, 2026)
This article details the values and interests inherent in the customary forest management practices of the peoples of the Old-Balinese village of Tenganan Pegringsingan in East Bali, highlights social justice from a planning perspective, and analyses the challenges villagers face in their pursuit of cultural recognition. It highlights the spiritual and ecological ties the Balinese have historically had to forests, which are seen as sacred spaces that contribute to cultural continuity and environmental balance. Despite this, modern management often overlooks these intangible values, causing ecological and social issues. Through ethnographic methods, including participant observation and interviews with traditional leaders and community members from 2022 to 2023, and drawing on earlier fieldwork from 2010 to 2012, the study finds that community-based values guide forest resource management. These values encompass protocols governing human relationships with the forest, residents' perceptions of the forest as a protector and marker of identity, and the forest's role as a spiritual space.